Emotions triggered by live arthropods shed light on spider phobia - Frynta, Daniel; Janovcová, Markéta; Štolhoferová, Iveta; Peléšková, Šárka; Vobrubová, Barbora; Frýdlová, Petra; Skalíková, Hana; Šípek, Petr; Landová, Eva (Scientific reports, 2021)
Spiders are mostly harmless, yet they often trigger high levels of both fear and disgust, and arachnophobia (the phobia of spiders) ranks among the most common specific animal phobias. To investigate this apparent paradox, we turned to the only close relatives of spiders that pose a real danger to humans: scorpions. We adopted a unique methodology in order to assess authentic emotions elicited by arthropods. Over 300 respondents were asked to rate live specimens of 62 arthropod species (including spiders, scorpions, cockroaches, and other insects) based on perceived fear, disgust, and beauty. We found that species' scores on all three scales depended on the higher taxon as well as on body size. Spiders, scorpions, and other arachnids scored the highest in fear and disgust, while beetles and crabs scored the highest in beauty. Moreover, all chelicerates were perceived as one cohesive group, distinct from other arthropods, such as insects or crabs. Based on these results, we hypothesize that the fear of spiders might be triggered by a generalized fear of chelicerates, with scorpions being the original stimulus that signals danger.
Keywords: Male; Spiders; emoce; lidé středního věku; pavouci; Animals; strach; Surveys and Questionnaires; shluková analýza; Cluster Analysis; Humans; Middle Aged; senioři; mužské pohlaví; Fear; Female; mladiství; členovci; Arthropods; Aged; Phobic Disorders; fobie; ženské pohlaví; průzkumy a dotazníky; mladý dospělý; Adult; zvířata; Young Adult; Adolescent; dospělí; lidé; Emotions